The COVID-19: PENGARUH PROMOSI KESEHATAN PADA SWAMEDIKASI MENGGUNAKAN VITAMIN DI ERA PANDEMI COVID-19 DENGAN METODE CARA BELAJAR INSAN AKTIF ( CBIA ) - Endah Sri Lestari; Titien Siwi Hartayu; Nunung Priyatni (Universitas Kristen Immanuel, 2022)
The COVID-19 pandemic, which was set at the beginning of 2020, requires people to make changes related to their daily lifestyle habits. Starting from limiting themselves to interact or social distancing, using masks when outside the house, and washing hands frequently. Apart from maintaining social distance, people must also maintain their immune system to avoid Covid-19. This is usually done by taking a variety of vitamins and supplements. This study aims to increase the knowledge, attitudes and actions of PKK mothers in the Panggungharjo Village, Sewon District in using vitamins during the Covid-19 pandemic. This study uses a quantitative method with a quasi-experimental design with a pretest-posttest design with a control group. The research instrument used a booklet and a questionnaire. The normality test using the Kolmogorov-Smirnov method showed that the knowledge variable was not normal. Homogeneity test using Levene's method. The data of the intervention and control groups showed that all data were homogeneous P > 0.05. The statistical test was continued with the Wilcoxon method which showed that there was a significant change in the knowledge variable pretest - posttest I in the intervention group p = 0.00 < 0.05 so that Ho was rejected. Knowledge of pretest - posttest III in the control group obtained p = 0.036 > 0.05 so that Ho is accepted. In the attitude variable, the results obtained were Ho was accepted in the intervention group, P value = 0.506 and Ho was rejected in the control group with P value = 0.042. The action variable showed a significant change where Ho was rejected in the intervention group with a P value of 0.000 and the control group with a P value of 0.051. Thus the CBIA method is effective in increasing knowledge and action on the use of vitamins in the Covid-19 era.